Pengembangan Media Buletin Berbasis Etnomatematika untuk Meningkatkan Kemampuan Pemahaman Matematis - Jannah, Iftah Miftahul; Maulana, Maulana; Isrokatun, Isrokatun (Jurnal Pena Ilmiah, 2021)
This research focuses on the development of ethnomathematical bulletin media to improve students' mathematical understanding. Research Development with ADDIE design consists of five stages, they are analysis, design, development, implementation, and evaluation. The sample taken is class IV SDN 1 Buyut. Sampling was done by purposive method. The research instruments used were mathematical understanding tests, expert validation questionnaires, observation sheets, and interview guidelines. Based on the validation of material and media experts, the ethnomathematics bulletins were considered valid with a total percentage of 80 and 76%, respectively. After doing the feasibility test, the ethnomathematical bulletin media was considered suitable for use with a percentage of 78%. In a limited trial, it was also known that the bulletin media could increase students' understanding. These results are in line with the findings at the implementation stage, where it is known that the bulletin media has an effect on increasing students' mathematical understanding.